A comparative study of norethisterone and combined oral contraceptive pill in the treatment of dysfunctional uterine bleeding - Sayantan Sen; Tapan Kumar Mandal; Arijit Dutta; Himel Mondal; Tufan Khalua (CHRISMED Journal of Health and Research, 2019)
Background: A significant percentage of women in India suffer from dysfunctional uterine bleeding (DUB), which has a negative impact on physical and social life. Norethisterone and low-dose combined oral contraceptive (COC) pills are used in the treatment of DUB. Aim: The aim of this study was to compare the efficacy and safety of norethisterone and low-dose COC pills in reduction of blood loss in DUB. Materials and Methods: A prospective randomized interventional study was conducted with patients with DUB. Pretreatment pictorial blood loss assessment chart (PBAC) and hemoglobin in blood were obtained from patients. Then, Group I (n = 50) and Group II (n = 50) patients were provided treatment with norethisterone and low-dose COC pills, respectively. Posttreatment PBAC and hemoglobin level in blood was obtained after 6 months of treatment. Improvements in PBAC and hemoglobin level (difference between posttest and pretest value) were compared by unpaired t-test with α = 0.05. Results: Mean age of Group I and Group II patients was 28.62 ± 9.84 and 28.42 ± 10.08 years, respectively. Improvement in PBAC score in patients treated with norethisterone versus low-dose COC pill was −98.62 ± 7.82 versus −96.44 ± 8.74 (P = 0.19). Improvement in hemoglobin level in patients treated with norethisterone versus low-dose COC pill was 2.75 ± 1.06 gm/dL versus 2.71 ± 0.86 gm/dL (P = 0.84). Conclusion: Norethisterone and low-dose COC pills were found to be equally efficacious in reducing bleeding in DUB. Hence, any one of the drugs can be used in the treatment of DUB according to patients' profile. However, considering the side effects, low-dose COC pills may be a better choice.